HEALTHY SMILES OF KINDERGARTEN CHILDREN: EARLY DETECTION OF DENTAL CARIES AND SOCIALISATION ON HOW TO MAINTAIN ORAL HYGIENE: SENYUM SEHAT ANAK TK: DETEKSI DINI KARIES GIGI DAN SOSIALISASI CARA MENJAGA KEBERSIHAN GIGI DAN MULUT - Arshy Prodyanatasari; Djembor Sugeng Walujo; Khansa Maritza Azzahro; Dita Salma Clarabella; Tria Wulandari Milenia; Zahra Aulia Devita Sari; Jewell Renanda Ardita Setiawan; Ida Royani (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
Dental caries remains a significant health problem among young children, especially in kindergarten.Data indicate a high prevalence of caries among children aged 4-6 years in Indonesia, which is attributed to a lack of knowledge about dental hygiene, improper toothbrushing techniques, and a habit of consuming sugary foods. This community service activity was conducted as an effort to detect and prevent dental issues early on, as childhood is a critical period for establishing healthy lifestyle habits. The objectives of this activity are: (1) To conduct early detection of dental caries; (2) To enhance children's and teachers' knowledge about oral health, and (3) To train proper brushing techniques through interactive educational approaches. The community service was conducted at Dharma Wanita Kindergarten, Kediri, involving 40 children aged 4–6 years. The methods used included: (1) Dental examinations, (2) Interactive education through lectures, demonstrations of toothbrushing using audio- visual media such as videos on proper toothbrushing techniques, jaw models (phantoms), and educational games, and (3) Knowledge assessment through pretest-posttest questionnaires. Data were analysed using quantitative descriptive analysis. The results showed that 72% of students had dental caries. Following the education, there was an improvement in students' understanding of how to maintain dental and oral health, as well as how to brush their teeth properly. The toothbrushing demonstration successfully improved the children's skills, with 95% able to practise the correct technique. Teachers responded positively to the programme. This activity was effective in increasing awareness and promoting dental health practices among preschool children. Collaboration between health workers and schools is essential for the sustainability of the programme. Recommendations: (1) Regular monitoring by the community health centre, (2) Integration of dental health materials into the early childhood education curriculum, and (3) Development of school dental health cadres.